A-Z of nutritional supplements: dietary supplements, sports nutrition foods and ergogenic aids for health and performance: Part 41 - Ranchordas, M. K.; Lundy, B.; Burke, L. M.; Stear, S. J.; Castell, L. M. (British Journal of Sports Medicine, 2013)
Vitamin preparations have been a stalwart of the supplement industry. They reflect both our understanding that they are, by definition, essential for optimal health and function, as well as our fears that either the food supply, or the way we consume it, fails to provide us with optimal amounts of these micronutrients. In the case of B-vitamins, the greatest research interest in supplementation occurred around World War II, tied to the reasonably new discovery of many of these vitamins and the interest in adequate war rations and military feeding plans. Even with the more targeted interest in sports nutrition, the topic of vitamin supplementation seems dated, with most available studies dating back to the early 1990s. The interest in vitamin K in sports nutrition, however, is more contemporary, due to its role in bone health.